Entrepreneurial Intention of MSME Actors in Indonesia: An Empirical Study on the Influence of Entrepreneurship Learning and the Moderating Role of Subjective Norms - Indra Gunawan; Rhian Indradewa; Unggul Kustiawan (International Journal of Engineering, Science and Information Technology, 2025)
Entrepreneurship is one of the strategic pillars in driving national economic growth, particularly through the role of Micro, Small, and Medium Enterprises (MSMEs), which contribute more than 60% of Indonesia’s Gross Domestic Product (GDP). This study aims to analyse the factors affecting entrepreneurial intention among MSME actors in Indonesia who have participated in entrepreneurship training. Specifically, the study examines the influence of entrepreneurial motivation, market orientation, entrepreneurial orientation, entrepreneurial learning, entrepreneurial attitude, and entrepreneurial self-efficacy on entrepreneurial intention, as well as testing the role of subjective norms as a moderating variable. Using a quantitative approach and the Partial Least Squares Structural Equation Modelling (PLS-SEM) method, data were collected from 380 MSME respondents across the Greater Jakarta area. The findings reveal that entrepreneurial learning significantly mediates the relationship between market orientation and entrepreneurial intention, as well as between entrepreneurial motivation and entrepreneurial intention. Meanwhile, subjective norms were found to moderate the relationship between entrepreneurial attitude and entrepreneurial intention, but not the relationship between entrepreneurial self-efficacy and intention. These findings contribute theoretically to the understanding of the cross-path relationships between psychological and contextual variables in shaping entrepreneurial intention. In practical terms, entrepreneurship training should be designed to strengthen active learning and foster social norms that support entrepreneurial intention.